Dynamic behavior of HTSC opening switch models controlled by short over-critical current pulses - Agafonov, A.V.; Krastelev, E.G.; Mikhalev, P.S.; Voronin, V.S. (Вопросы атомной науки и техники, 1999)
Dynamical properties of thin epitaxial film of YBa₂Cu₃O₇ HTSC-opening switch models under action of short overcritical current pulses were measured to test this method of control of fast (of nanosecond range) high-power opening switches for accelerator applications.